Here's the question you clicked on:
MrOrbit
Let k(x) = x^5 + 3x -2 and let k^-1 denote the inverse of k. Then, find (k^-1)'(2)
actually in such cases u dont need to find the inverse itself and differentiate it... so what is the formula for the derivative of inverse?
\[(f^{-1}(x))'=\frac{1}{f'(f^{-1}(x))}\]am i right ?
how about the asker? are u familiar with that formula?
ok i gotta go but here are some hints for u MrOrbit\[(f^{-1})'(2)=\frac{1}{f'(f^{-1}(2))}\]so all that u need is finding\[f^{-1}(2)\]for reaching there note that\[f(1)=2\]